Twelve new species-group replacement names and further nomenclatural notes on Lycaenidae (Lepidoptera) - Lamas, Gerardo (Zootaxa, 2008)
Twelve new species-group names in Lycaenidae are proposed to replace invalid ones due to primary or secondary homonymy: Arhopala ariana wanggu (for Arhopala ariana hainana Wang & Gu, 1997), Arhopala paraganesa felipa (for Arhopala paraganesa hayashii Schröder & Treadaway, 2002), Arhopala paraganesa insula (for Panchala paraganesa hainana Wang & Gu, 1997), Favonius leechina (for Thecla orientalis leechi Riley, 1939), Jamides cleodus sunadyl (for Lampides cleodus lydanus Fruhstorfer, 1916), Lycaena aditya charmesse (for Lycaena aditya churkini Charmeux & Desse, 2006), Lycaena alpherakii sergeii (for Thersamonia alpherakii zhdankoi Churkin, 2002), Megisba strongyle miskinigra (for Lycaena nigra Miskin, 1890), Plebejus (Agriades) glandon manitoba (for Plebeius aquilo var. lacustris Freeman, 1939), Plebejus (Albulina) orbitulus chaos (for Albulina tibetana D'Abrera, 1993), Plebejus (Vacciniina) fergana nikolaii (for Vacciniina fergana rubini Churkin, 2006), and Plebejus (Plebejides) pylaon tumultus (for Plebejus (Plebejides) pylaon forsteri Bálint, 1990). Nine oher junior secondary homonyms are discussed, but no new replacement names are proposed for them because they are no longer considered congeneric with their senior homonyms. Attention is called to three further junior primary homonyms in use which need to be referred to the International Commission on Zoological Nomenclature for a ruling under its plenary power.